Investigating the relationship between the English instruction time decrease and English learning achievements - Didi Sukyadi; Lukman Hakim (Indonesian Journal of Applied Linguistics, 2023)
This study examines the link between an English instructional time decrease on English learning achievements by reviewing the students’ trends of English learning achievement scores from 2011 to 2017 and conducting a survey concerning the decline in their instructional time. A mixed-method approach was used to meet the objective of the research. For quantitative data, the Likert-scale questionnaire was collected from 474 senior high school English teachers all over Indonesia, and the achievement data consisted of 211,086 summative scores of senior high school students from semesters 1 to 5. For qualitative data, the respondents filled in open-ended questions unveiling their viewpoints on instructional time decrease. The result between the correlation analysis and the teacher’s open-ended question seems inconsistent. Even though the statistical analysis does not indicate any direct relationship between instructional time decrease and students’ achievement where both summative and proficiency scores keep increasing during the period observed, from the teachers’ perspective, questionnaire data reported a significant tendency for the reduction in instructional time on learning achievement. Further analysis shows that in terms of students’ learning achievement and proficiency, instructional time decrease cannot be stated as a factor that directly influences students’ learning. However, from the teachers’ perspective, the reduction is believed to influence their students’ achievement and classroom management.